TREATING MULTIPLE SCLEROSIS WITH CLADRIBINE. Issue 12 (15th November 2016) - Alvarez-Gonzalez, C; Allen-Philbey, K; Mathews, J; Turner, BP; Baker, D; Gnanapavan, S; Marta, M; Giovannoni, G; Schmierer, K
Abstract : Background: Evidence suggests Cladribine is a highly effective, safe and convenient disease modifying treatment (DMT) for people with multiple sclerosis (pwMS). We report our experience using Cladribine in pwMS. Methods: Cladribine was offered to pwMS with clinical and/or MRI disease activity, however restricted choice of DMT. Treatment cycles consisted of Cladribine administered as subcutaneous injections over a total of up to 6 days (10 mg/day) in 5 weeks, adjusted to individual lymphocyte counts. Results: Seventeen pwMS (ten women and seven men) have had a first treatment cycle of Cladribine. Mean age was 44 years (34–60 years), median EDSS was 5 (2–8). No acute side effects were observed. Lymphocyte counts dropped from a mean of 1.81×10*9/L (Range: 0.9–3.4) at baseline to 1.41×10*9/L (0.7–3) 4 weeks after starting treatment, and to 1.02×10*9/L (0.6–1.6) 4 weeks later. Other white cell counts were not affected. No serious treatment-related adverse event was observed. No clinical MS disease activity was observed after a mean follow-up of four months (1–15). Conclusion: Cladribine was well tolerated and led to an expected drop in lymphocyte counts leaving other cell lines unaffected. Long term follow-up is underway to evaluate the effect of Cladribine in pwMS.